WORKSHOP SENI MERANGKAI BUNGA SEBAGAI PELUANG USAHA KREATIF BAGI IBU-IBU JEMAAT GKPI KHUSUS TELADAN - Gultom, Pesta; Manik, Desma Erica Mariati; Nainggolan, Elisabeth; Gea, Sanderwan Kristian; Hoki, Fernando (Universitas Methodist Indonesia, 2023)
As knowledgeable people, lecturers are required to educate and advance people's lives. Therefore it is mandatory to carry out community service activities, as proof of the contribution of the lecturers. Lecturers are required to contribute their abilities, both in the fields of knowledge, energy, and materials. Community service programs are carried out through direct interaction through lectures, discussions and practices. The participants as partners are the women members of the GKPI Congregation for Exemplary Church. With this PkM program it can increase the creativity of mothers, through knowledge of interesting flower arrangement techniques, it can be used as new business opportunities so that new entrepreneurs are created.